Innovative green consumption in a manufacturing company in the environmental-based view approach: the role of moral obligation, TPBF, green intention and pro-environmental behavior with the moderating effect of innovative work environment - Muhammad Naparin; Widhy Tri Astuti (Cogent Business & Management)
Although the contribution of the manufacturing to gross domestic product is very large, its negative impact on the environment has not been resolved. To answer this challenge, the behavior of employees and workers in consuming natural resources must provide innovative solutions to environmental issues, called innovative green consumption (IGC). This study answers what variables influence the IGC and how the interactions between these variables occur. This aimed to analyze the influence of the theory of planned behavior framework (TPBF) and perceived moral obligation (PMO) on green intention (GI) and pro-environmental behavior (PEB), the influence of PEB on IGC, and the moderating and direct influence of an innovative work environment (IWE) on IGC. This was a quantitative method. The research model was tested on 214 employees and workers at a manufacturing company. Results: TPBF and PMO had a significant influence on GI and PEB. PEB and IWE had a significant influence on IGC, and IWE had significantly moderated the influence of PEB on IGC. The implications for academics, policy makers, and professionals are opening up a new paradigm in innovative consumption patterns for sustainability. Originality: It reconstructs IGC as a new paradigm in the manufacturing industry and provides a new understanding of IGC antecedents based on moral, intentions, and behavior perspectives.